Impact of cover cropping on root lesion nematodes (Pratylenchus spp.) and nematode communities in Narcissus fields - Vongai Chekanai; Roy Neilson; David Roberts; Simon G. Edwards; Matthew A. Back (Applied Soil Ecology, 2026)

Temporal monitoring of free-living nematode communities for evaluation of soil health in an arable crop rotation - Ana I.M. Natalio; Mohammed Ahmed; Matthew A. Back; Andrew Richards; Simon Jeffery (Pedobiologia, 2024)

Field-scale heterogeneity overrides management impacts following conversion to no-till within an arable system - Ana I.M. Natalio; Matthew A. Back; Andrew Richards; Simon Jeffery (Applied Soil Ecology, 2024)

Coexistence between similar invaders: The case of two cosmopolitan exotic insects - Matthew B. Arnold; Michael Back; Michael Daniel Crowell; Nageen Farooq; Prashant Ghimire; Omon A. Obarein; Kyle E. Smart; Trixie Taucher; Erin VanderJeugdt; Kayla I. Perry; Douglas A. Landis; Christie A. Bahlai (Ecology, 2023)
Biological invasions are usually examined in the context of their impacts on native species. However, few studies have examined the dynamics between invaders when multiple exotic species successfully coexist in a novel environment. Yet, long‐term coexistence of now established exotic species has been observed in North American lady beetle communities. Exotic lady beetles Harmonia axyridis and Coccinella septempunctata were introduced for biological control in agricultural systems and have since become dominant species within these communities. In this study, we investigated coexistence via spatial and temporal niche partitioning among H. axyridis and C. septempunctata using a 31‐year data set from southwestern Michigan, USA. We found evidence of long‐term coexistence through a combination of small‐scale environmental, habitat, and seasonal mechanisms. Across years, H. axyridis and C. septempunctata experienced patterns of cyclical dominance likely related to yearly variation in temperature and precipitation. Within years, populations of C. septempunctata peaked early in the growing season at 550 degree days, while H. axyridis populations grew in the season until 1250 degree days and continued to have high activity after this point. C. septempunctata was generally most abundant in herbaceous crops, whereas H. axyridis did not display strong habitat preferences. These findings suggest that within this region H. axyridis has broader habitat and abiotic environmental preferences, whereas C. septempunctata thrives under more specific ecological conditions. These ecological differences have contributed to the continued coexistence of these two invaders. Understanding the mechanisms that allow for the coexistence of dominant exotic species contributes to native biodiversity conservation management of invaded ecosystems.